Ownership and Control in Outsourcing To China: Estimating the Property-Rights Theory Of the Firm* - Feenstra, Robert C.; Hanson, Gordon H. (Quarterly Journal of Economics, 2005)
In this paper, we develop a simple model of international outsourcing and apply it to processing trade in China.We observe China's processing exports broken down by who owns the plant and by who controls the inputs the plant processes.Multinational firms engaged in export processing in China tend to split factory ownership and input control with managers in China: the most common outcome is to have foreign factory ownership but Chinese control over input purchases.To account for this organizational arrangement, we appeal to a property-rights model of the firm.Multinational firms and the Chinese factory managers with whom they contract divide the surplus associated with export processing by Nash bargaining.Investments in input search, production, and marketing are partially relationship specific.In our benchmarks estimates, this relationship specificity is lowest in southern coastal provinces, where export markets are thickest, and highest in interior and northern provinces.The probability contracts are enforced has a similar pattern and is the lowest along the southern coast and the highest in the north.